Reference ranges of placental volume measured by virtual organ computer‐aided analysis between 10 and 14 weeks of gestation. Issue 4 (6th February 2017) - Meengeonthong, Daranee; Luewan, Suchaya; Sirichotiyakul, Supatra; Tongsong, Theera
ABSTRACT: Objective: To establish the reference ranges of the placental volume between 10 and 14 weeks of gestation of Thai fetuses. Methods: The placental volumes were acquired in normal pregnancies between 10 and 14 weeks of gestation using transabdominal three‐dimensional ultrasound. The placental volume was then analyzed using VOCAL (virtual organ computer‐aided analysis) technique with a rotation angle of 30°. The measured values were regressed to identify the best‐fit model. Results: A total of 236 volume datasets met the inclusion criteria and were used for offline analysis. Placental volume significantly increased with increasing crown‐rump length (CRL). The best‐fit regression models for predicted mean and SD as a function of CRL, available for z score calculation and construction of the percentile chart, are as follows: ln ( placental volume ) = ln ( 0.187 ) + 1 . 375 × ln ( CRL in mm ) ( r = 0.824 ; p < 0.001 ), Predicted SD = − 0. 895 + ( 0.266 × CRL in mm ) ( r = 0.190 ; p < 0.001 ) . Conclusion: Reference ranges of placental volume have been constructed. This normative data may be a useful tool in the evaluation of various conditions affecting placental size, eg, fetal hemoglobin Bart's disease. © 2016 Wiley Periodicals, Inc. J Clin Ultrasound 45 :185–191, 2017;